“Factores de motivación, en la enseñanza aprendizaje de matemática: funciones y ecuaciones cuadráticas, bloque 1, unidad 2, en los estudiantes de 1° de bachillerato general unificado de la unidad educativa del milenio Penipe del cantón Penipe, provincia de Chimborazo, período septiembre 2015 - marzo 2016.” - Ibarra Berrones, Elena del Rocío (2016)
The present research study entitled: Motivational factors in the teaching and learning process of math: functions and quadratic equations, area 1, unit 2, aimed at the students enrolled in the first year of baccalaureate in an educational institution called “Penipe” located in Penipe, province of Chimborazo, with the aim to determine if teachers motivate students mainly with their tone of voice, temperament, physical appearance, and the empathy to transmit information to students in order to raise the student´s interest to learn math with the assistance of tangible and non-tangible resources to achieve meaningful learning as it is well-known that teachers do not apply innate basic strategies which were developed in their technical training that ends up in the student´s lack of attention. It is evident that students dislike math just by looking at their face followed by a sort of frustration when they do not comprehend and take too literally the way to resolve an exercise. Apart from being a real inconvenient in the moment, it goes beyond as teachers themselves transmit the message that math is a complex subject. It is a descriptive study as the information is obtained from the students. To verify the study, the instrument for data collection was a survey which was applied to 66 students. The information was statistically processed with the assistance of informatics tools. In conclusion, it can be said that teachers of mathematics do not apply basic motivational strategies to encourage students to learn the subject. It is essential to recommend educators to generate a better learning environment for their students.